Multimodality imaging and three‐dimensional printed model in patients with left ventricular outflow tract obstruction. (11th December 2019) - Hamatani, Yasuhiro; Shiraishi, Isao; Nishii, Tatsuya; Okada, Atsushi; Amaki, Makoto; Yamasahita, Kizuku; Matsumoto, Yorihiko; Kanzaki, Hideaki; Fukuda, Tetsuya; Fujita, Tomoyuki; Yasuda, Satoshi; Kobayashi, Junjiro; et al.
Abstract: Surgical treatment is an effective therapy and the gold standard for patients with left ventricular outflow tract obstruction (LVOTO) and drug‐refractory symptoms. However, it is difficult to arrange a concrete surgical plan due to the heterogenous and complex cardiac anatomy. Three‐dimensional (3D) printing is an emerging technology that is able to reproduce complex cardiac anatomy. Here, we present two patients with LVOTO in whom we created 3D printed models. In these two patients, we compared the 3D printed model and the intraoperative findings and confirmed that the 3D printed model we created could reproduce the complex cardiac anatomy including the interventricular septum, papillary muscles, and abnormally thickened chordae. By using 3D printed models, cardiologists and surgeons can comprehend the complex 3D cardiac structure and spatial positional relationship preoperatively and perform surgical rehearsal. 3D printing could be a valuable tool for the management of patients with LVOTO.